Feasibility and Preliminary Efficacy of Gait Training Assisted by Multichannel Functional Electrical Stimulation in Early Stroke Rehabilitation: A Pilot Randomized Controlled Trial. (February 2021) - van Bloemendaal, Maijke; Bus, Sicco A.; Nollet, Frans; Geurts, Alexander C. H.; Beelen, Anita
Background . Many stroke survivors suffer from leg muscle paresis, resulting in asymmetrical gait patterns, negatively affecting balance control and energy cost. Interventions targeting asymmetry early after stroke may enhance recovery of walking. Objective . To determine the feasibility and preliminary efficacy of up to 10 weeks of gait training assisted by multichannel functional electrical stimulation (MFES gait training) applied to the peroneal nerve and knee flexor or extensor muscle on the recovery of gait symmetry and walking capacity in patients starting in the subacute phase after stroke. Methods . Forty inpatient participants (≤31 days after stroke) were randomized to MFES gait training (experimental group) or conventional gait training (control group). Gait training was delivered in 30-minute sessions each workday. Feasibility was determined by adherence (≥75% sessions) and satisfaction with gait training (score ≥7 out of 10). Primary outcome for efficacy was step length symmetry. Secondary outcomes included other spatiotemporal gait parameters and walking capacity (Functional Gait Assessment and 10-Meter Walk Test). Linear mixed models estimated treatment effect postintervention and at 3-month follow-up. Results . Thirty-seven participants completed the study protocol (19 experimental group participants). Feasibility was confirmed by good adherence (90% of the participants) and participant satisfaction (median score 8). Both groups improved on all outcomes over time. No significant group differences in recovery were found for any outcome. Conclusions . MFES gait training is feasible early after stroke, but MFES efficacy for improving step length symmetry, other spatiotemporal gait parameters, or walking capacity could not be demonstrated. Trial Registration . Netherlands Trial Register (NTR4762).